Stimuli-responsive Polymeric Nanosystems for Therapeutic Applications - Handa, Mayank; Singh, Ajit; Flora, Swaran Jeet Singh; Shukla, Rahul (Current Pharmaceutical Design, 2022)
Background: Recent studies have been reported emerging polymeric nanoparticles as a promising particulate carrier system for controlled and targeted drug delivery. Stimuli-responsive nanocarriers have shown characteristics, such as high drug uptake at specific sites or targeted cells with an advantage of no drug leakage. These stimuli-responsive polymeric systems are used to functionalize nanocarriers, such as dendrimers, metallic nanoparticles, polymeric nanoparticles, liposomal nanoparticles, and quantum dots. Objective: The study reviews the potential of smart stimuli-responsive carriers for therapeutic application and their behavior in external or internal stimuli, like pH, temperature, redox, light, and magnetic field. These stimuli- responsive drug delivery systems exhibit different drug release patterns in in vitro and in vivo studies. Stimuli- responsive nanocarriers are useful for both hydrophilic and hydrophobic drugs and release them on applied stimulus. This review highlights the recent development in the physical properties of polymeric materials and their application in stimuli-responsive specific drug delivery. Conclusion: The stimuli (smart, intelligent, programmable) drug delivery systems provide site-specific drug delivery with potential therapy for cancer, neurodegenerative, and lifestyle disorders. The stimuli-responsive- based nanocarriers are developing at a fast pace, and there is a huge demand for biocompatible and biodegradable responsive polymers for effective and safe delivery.
Keywords: temperature responsive